Effects of triflute pin geometry on defect formation and material flow in FSW using CEL approach - Mostafa Akbari; Parviz Asadi (Journal of Advanced Joining Processes)
Complicated tool pin designs in Friction Stir Welding (FSW) need to be considered in terms of material flow and defect formation. This study investigates the effects of the triflute tool's geometrical parameters on temperature, strain, void formation, and material mixing using a numerical method. The numerical model employs a coupled Eulerian-Lagrangian (CEL) formulation and successfully predicts void formation and material mixing during friction stir welding (FSW). Four tool pin designs are considered for material flow, including one cylindrical pin and three triflute pins with flute radii of 1 mm, 1.5 mm, and 2 mm. The findings indicate that the stir zone is divided into shoulder-driven and pin-driven zones, each exhibiting distinct material flow patterns. In the shoulder-driven zone, material flow toward the advancing side is dominant, while in the pin-driven zone, it flows toward the retreating side. Flutes on the FSW pin tool increase the sweeping rate, strain, and material movement in the stir zone. However, flutes with a larger radius sweep a greater amount of material and thus require more softened material to facilitate movement. Therefore, for defect-free joint formation, a higher rotational speed of the tool will be required, which may adversely affect tool lifespan and joint mechanical properties. The effectiveness of flutes with a smaller radius of 1 mm is significantly greater than that of those with a larger radius (1.5 or 2 mm) in enhancing material flow and achieving defect-free welding.